A Graph Based Framework for Route Optimization in Sea-Trade Logistics. (25th October 2015) - Chu, Dianhui; Li, Chunshan; Xu, Xiaofei; Zhang, Xiaofeng
Abstract : How to find the optimal transportation route in sea-trade is very important for the logistics industry. The traditional routing problem is solved by performing the combinatorial optimization over a specified transportation network. Facing the huge network extracted from the foreign trading industry as well as the complex constraints, it is impossible for the traditional optimization methods to find the solution in a short time, which motivates our work. In this paper, we first carefully study the property of foreign trade network, and then convert the transportation network into a hierarchical one and propose a novel framework based on graphical model to solve this large scale network optimization problem. The experimental results demonstrate that our approach is superior to the famous ant colony optimization algorithm (ACO) in terms of accuracy and the time spent.